2020
DOI: 10.5994/jei.16.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Masa hidup imago, progeni, dan kemampuan parasitisasi Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae), parasitoid kutu putih singkong

Abstract: Parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) diintroduksikan dari Thailand ke Indonesia pada tahun 2014 untuk mengendalikan hama asing invasif, kutu putih singkong Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). Penelitian dilakukan di laboratorium dengan tujuan untuk mengetahui potensi reproduksi, pengaruh pemberian larutan madu terhadap masa hidup imago, mempelajari keperidian, progeni, dan respons A. lopezi terhadap peningkatan kerapatan inang. Penelitian dilaksa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The relationship between parasitization level and host density is important in the dynamics of parasitoid and host populations. Previous studies revealed that a host density of 2-100 had a substantial influence on the quantity of P. manihoti parasitized by A. lopezi [32,33]. The parasitoid Anagyrus kamali, which parasitized Maconellicoccus hirsutus, was likewise impacted by host density in terms of parasitization, progeny, and sex ratio [34,35,36].…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between parasitization level and host density is important in the dynamics of parasitoid and host populations. Previous studies revealed that a host density of 2-100 had a substantial influence on the quantity of P. manihoti parasitized by A. lopezi [32,33]. The parasitoid Anagyrus kamali, which parasitized Maconellicoccus hirsutus, was likewise impacted by host density in terms of parasitization, progeny, and sex ratio [34,35,36].…”
Section: Discussionmentioning
confidence: 97%